Cultural competence in critical care nurses and its relationships with empathy, job conflict, and work engagement: a cross-sectional descriptive study - Mohsen Soleimani; Sajad Yarahmadi (BMC, 2023)
Abstract Background Cultural competence is more important than ever for nurses today; therefore, it may be helpful to learn more about it and examine how it relates to empathy, job conflict, and work engagement. The purpose of this study was to determine (a) the level of cultural competence, empathy, job conflict, and work engagement; (b) the relationship between cultural competence, demographic information, and main variables; (c) the predictors of cultural competence among critical care nurses. Methods A multicenter, descriptive cross-sectional study was conducted in Iran from August to October 2022. Through convenience sampling, 153 critical care nurses from three hospitals participated. The research tool consisted of five parts: Demographic information questionnaire, Cultural Competence Questionnaire, Jefferson Scale Empathy, Dobrin Job Conflict, and Utrecht Work Engagement, which were collected by paper self-report. Descriptive statistics, the correlation between variables, and linear regression were used to analyze the data. Results Among critical care nurses (response rate 79.27%), the mean (SD) scores for cultural competence, empathy, job conflict, and work engagement were 74.05 (7.96), 83.44 (29.17), 11.00 (2.38), and 43.69 (16.33), respectively. There was a significant correlation between cultural competence and age (r = 0.46, p = 0.001), marital status (r = 0.27, p = 0.004), academic degree (r = 0.44, p = 0.001), work experiences (r = 0.43, p = 0.001), empathy (r = 0.50, p = 0.001), and job conflict (r=-0.16, p = 0.049). Academic degree (β = 0.36, p < 0.001) and empathy (β = 0.26, p < 0.001) were significant explanatory variables that predict cultural competence. Conclusion In Iranian critical care nurses, cultural competence and job conflict were moderate, empathy was good, and work engagement was poor. There was a significant relationship between cultural competence, age, marital status, academic degree, work experiences, empathy, and job conflict. Academic degree and empathy predict cultural competence.